The Level of students' mathematical creative thinking skills as measured by their self-confidence - Efwan, Neng Syntadewi; Afriansyah, Ekasatya Aldila; Luritawaty, Irena Puji; Arwadi, Fajar; Yadav, Dharmendra Kumar (Universitas Terbuka, 2024)
High self-confidence and creative mathematical thinking skills will change students from having difficulty with mathematics to active learners who can solve mathematical problems. But the facts show that the achievement of both abilities is still quite low. The purpose of this research is to analyze how students' creative mathematical thinking skills are viewed from the perspective of self-confidence in social arithmetic material. Social arithmetic material is used because it allows them to abstract mathematical processes into their daily lives, thereby developing their creativity. The research method is descriptive qualitative. The sample was 3 people, namely 1 person for each level of self-confidence (high, medium, and low). They are selected through purposive sampling. The data collection techniques used include questionnaires, tests, interviews, and field notes. The data analysis techniques employed are data reduction, data presentation, and conclusion drawing. The results indicate that students' self-confidence levels in social arithmetic material affect their creative mathematical thinking skills. It was found that students with high self-confidence were able to meet three indicators of creative mathematical thinking skills: fluency, flexibility, and elaboration. However, students with high self-confidence were not able to meet the originality indicator. Students with moderate self-confidence were able to meet one indicator of creative mathematical thinking skills, namely fluency, but were not able to meet the flexibility and elaboration indicators. Meanwhile, students with low self-confidence were not able to meet any indicators of creative mathematical thinking skills. Thus, self-confidence can be increased to improve mathematical creative thinking skills.